The influence of Financial Literacy and Self Control on Students’ Personal Financial Management in the Solo Raya Region - Mahanani, Riskillah Azizah; Hendar, Hendar (CV. ULIL ALBAB CORP, 2025)
This research seeks to examine how financial literacy and self-control impact students' personal financial management in the Solo Raya region, and to explore the mediating role of self-control in these relationships. The research method used is quantitative with an explanatory research approach. The research sample amounted to 150 students who were selected using non-probability sampling techniques, especially accidental sampling. Data collection was carried out through questionnaires that were analyzed using Structural Equation Modeling (SEM) with the help of Warp PLS software. The outcomes of the investigation show that financial literacy has a positive effect on self-control and personal financial management. Self-control also has a positive effect on personal financial management. In addition, self-control has been shown to play a mediator role in the association between financial literacy and personal financial management. These findings affirm the importance of improving financial literacy and self-control skills in supporting better financial management behavior among students. This research makes a practical contribution to the development of financial literacy programs that are integrated with character formation among students